MEMBANGUN SISTEM LINUX MANDRAKE MINIMAL MENGGUNAKAN INISIAL DISK RAM - Wagito Wagito (Faculty of Industrial Technology Universitas Islam Indonesia, 2006)
Minimal Linux system is commonly used for special systems like router, gateway, Linux installer and diskless Linux system. Minimal Linux system is a Linux system that use a few facilities of all Linux capabilities. Mandrake Linux, as one of Linux distribution is able to perform minimal Linux system. RAM is a computer resource that especially used as main memory. A part of RAM’s function can be changed into disk called RAM disk. This RAM disk can be used to run the Linux system. This paper explains how the Mandrake Linux system can be run in a RAM disk. The RAM disk which is used to run Linux system is loaded at the moment of initialization of Linux system. This RAM disk is called initial RAM disk (initrd). The Linux kernel which support initrd and a boot loader are needed to develop this system. The initrd file system that content Linux root system is created in this research. This initrd file is loaded into the RAM disk using a boot loader. This experiment shows that the Linux system can be run in the RAM disk. The Linux system that can be run is minimal Linux system because of the RAM disk capacity limitation.Keywords : minimal Linux, RAM disk, initrd